The trilemma of trade, monetary and immigration policies in the United States: Accounting for environmental sustainability - Alola, Andrew A. (Elsevier, 2019)
The United States like every other country across the globe, especially the developed nations, have consistently battled one of man's greatest challenge of the 21st century-saving and sustaining the dire environment. Being the largest emitter of carbon dioxide (CO2) after China, the United States is increasingly faced with an urgent policy drive toward environmental sustainability. Against the backdrop, this study employed the dynamic ARDL-bound testing approach to observing the tripartite impact of the trade policy, monetary policy, and migration index on carbon emissions over the period 1990:Q1-2018: Q2. The incorporated renewable energy consumption and the real GDP which controls for other unobserved factors arc observed to have similar and significant impacts as in previous studies. The current study found that the trade policy, monetary policy, and migration index exerts positive and significant impacts on carbon dioxide emissions in the long-am. It implies that. in the near future, the environmental sustainability of the United Rain is at the risk of the government policies on trade, monetary, and migration. However, such impact. of the migration index on the carbon dioxide emissions is barely significant. in the long-run and at the immediate time. Although the impact of the government's trade policy on carbon dioxide emissions is significant in the long-run, it immediate impact is negative and not significant. Hence, policy frameworks of the government should be designed such that it meets the Sustainable Development Goals 2030. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Sustainable environment; Carbon emissions; Trade policy; Monetary policy; Migration index; United States